JURIDICAL ANALYSIS OF NOVASI IN SETTLING DEBTS OF DEBTORS WHO EXPERIENCE INSOLVENCY IN INDONESIA - Sitompul, Mutiara Andiny (International Journal of Cultural and Social Science, 2026)
Insolvency is a state of the debtor's inability to fulfill its debt payment obligations which is normatively the basis of the bankruptcy mechanism in Indonesia. In the midst of the dominance of settlement through bankruptcy and Suspension of Debt Payment Obligations (PKPU), Indonesian civil law actually provides another alternative through the novation mechanism as stipulated in Article 1413 of the Civil Code. This study aims to analyze the position of novation as a mechanism for settling debts of debtors who experience insolvency and identify juridical obstacles in its application according to positive Indonesian law. This research is normative legal research with a legal and conceptual approach. The results of the study show that novation has legitimacy as a legitimate debt settlement mechanism outside of bankruptcy and PKPU, and can function preventively by removing old debts and replacing them with new engagements so as to prevent debtors from fulfilling the element of "due and collectible debts" as referred to in Article 2 of the UUKPKPU. However, the implementation of novation faces internal obstacles in the form of the legal terms of the agreement, the risk of loss of collateral, the ability of the debtor, and the potential for the cancellation of the novation due to defects in the old agreement. External barriers were also found in the form of the risk of cancellation through actio pauliana, as well as the absence of explicit provisions regarding novation in the UUKPKPU. Thus, although juridically novation has a legitimate position as a debt settlement mechanism, the effectiveness of its application to insolvent debtors is still limited by Indonesia's bankruptcy legal structure.